(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article is devoted to the use of gaming technologies in teaching mathematics. As one of the modern forms of this activity, the use of a mathematical quest is proposed. The article discusses the features of using the quest in teaching mathematics